Reoperation After Cholecystectomy. The Role of the Cystic Duct Stump. Issue 2 (1991) - Rogy, M. A.; Függer, R.; Herbst, F.; Schulz, F.
Abstract : The so-called "Postcholecystectomy Syndrome" may be due to various pathological biliary causes. The aim of this study was to evaluate the significance of the cystic duct stump syndrome and if so, how often a long (>1.5 cm) cystic duct stump was an indication for reoperation on the bile ducts after cholecystectomy in our patients. Three hundred and twenty two patients underwent a second operation on the bile ducts after cholecystectomy in the last ten years. In 35 patients (10.8%) a striking finding was a long cystic duct stump (>1.5 cm). In 24 of these patients, a pathological finding, in addition to the long cystic duct stump, was found on exploration. Out of these 24 patients there were 14 with common bile duct stones; 6 with stenosis of the sphincter of Oddi; 3 with chronic pancreatitis and in one patient hepatitis was the cause of the symptoms. From the remaining 11 patients 8 had a stone in a partial gall bladder or cystic duct stump. One patient had a fistula between the cystic duct stump and duodenum and one a suture granuloma. There was only one patient where a 1.5 cm long cystic duct stump remnant was the only pathological finding. Four years after reoperation this patient is still suffering from the same intermittent gastrointestinal symptoms. We conclude that the cystic duct stump is hardly ever a cause for recurrent symptoms in itself. Total excision of the cystic duct does not eliminate the existence of postcholecystectomy symptoms.